Infant action understanding: the roles of active training and motor development - Chung, Haerin; Filippi, Courtney A.; Woodward, Amanda L. (Frontiers in Developmental Psychology, 2024)
This study examined the potential interplay between motor development and intervention in support of action understanding. Eighty 9-month-old infants completed a tool-use training session and goal imitation paradigm that assessed action understanding in counterbalanced order. A metric of motor development was obtained using the Early Motor Questionnaire. Results indicated that training improved action understanding, particularly for those infants who started out with lower means-end skills. Results further indicated that infants who did not receive any training experience in the lab beforehand, drew on their existing means-end skills. These results emphasize independent contributions of training and motor development on action understanding and shed light on the interaction between training and individual motor readiness in facilitating action understanding in infancy.